Improving Demographic Diversity in the U.S. Air Force Officer Corps - Lim, Nelson (RAND Corporation, 2014)
Despite the Air Force's efforts to create a force that mirrors the racial, ethnic, and gender differences of the nation's population, minority groups and women are underrepresented in the active-duty line officer population, especially at senior levels (i.e., colonel and above). This report examines the reasons for this, with the goal of identifying potential policy responses.